KREATIVITAS GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN DI TAMAN-KANAK-KANAK - Penty Fatimah Panjaitan (Universitas Dharmawangsa, 2021)
Teachers are required to be creative in developing learning media by utilizing surrounding natural materials so that they can reduce costs. Each region has tremendous natural potential and can be used for the development of learning media in early childhood education. Such as: plants, wood shavings, wood waste from furniture, shells, and other natural materials. The creativity of teachers is required so that the learning process can be fun and varied so that children do not feel bored, with the variety of media used in early childhood learning, learning objectives can be achieved. Given the limited operational costs of TK/PAud educational institutions that cause the lack of media used in learning, the use of natural materials can be a solution in developing learning media that are cheap and easy to obtain from the surrounding environment but still prioritize aspects of security, comfort.Keywords: Teacher Creativity, Learning Media